A comprehensive list of asthmagens to inform health interventions in the Australian workplace. (11th November 2015) - Crewe, Julie; Carey, Renee; Glass, Deborah; Peters, Susan; Abramson, Michael J.; Benke, Geza; Reid, Alison; Driscoll, Tim; Fritschi, Lin
Abstract: Objective: To develop a comprehensive list of asthmagens which may occur in occupational settings in Australia. Methods: Potential asthmagens considered for this list were identified through work health and safety classification databases in Australia and through lists developed by professional associations in other countries. Inclusion criteria were: there is evidence that the agent is asthmagenic; it is used in occupational settings; and it is available in Australia. Results: The final list contained 277 asthmagens in 27 groups that may be found in occupational circumstances in Australia. Three other agents that have been documented as asthmagens in Australia were included: almond dust, fluoride (in aluminium pot room fumes); and sawdust from the Australian Blackwood. Conclusions: This is the first comprehensive and inclusive list of Australian occupationally relevant asthmagens to have been compiled. Implications: This list is specific for Australian workplace exposure to asthmagens. It will help focus policy and preventative practices and reduce the burden of occupational asthma. It will also be useful in future studies to identify those who are exposed to the asthmagens and provide information to assist regulators to identify industries, occupations, specific activities and existing exposure standards that can be targeted to improve worker health and welfare.